VD_FINDINFO Jug / 2011 / 287 vom 31. Oktober 2011 - VD Tribunal cantonal (2011)
PARTAGESENS GÉNÉRAL, PRESTATION DE PRÉVOYANCE, DIVORCE, INTÉRÊT MORATOIRE, INTÉRÊT RÉMUNÉRATOIRE | 122 al. 1 CC, 122 al. 2 CC, 22 al. 1 LFLP, 22 al. 2 LFLP, 15 al. 2 LPP, 7 OLP, 12 OPP2, 111 al. 1 LPA-VD